Contemporary Hollywood Crime Film and the New Individualism - Luis M. García-Mainar (European Journal of American Studies)
This article focuses on contemporary Hollywood films Silver City (2004), The Constant Gardener (2005) and The Departed (2006) in order to examine the intersection of the cultural discourse of the New Individualism, characterized by the helplessness and anxiety of the subject in the face of social change, with the generic conventions of the crime film. It explores the ways in which such conventions as crosscutting and suspense, the victim-hero of the thriller, or the trope of self-assertion through escape from the social space both articulate the New Individualism discourse and are transformed under its influence.